Heat-Resistant Polymers with Intense, Visible Photoluminescence Functionality and Fluorescence Probing Application - Masatoshi Hasegawa; Shunichi Horii (Macromol, 2023)
Heat-resistant polymers with an intense, visible photoluminescence (PL) functionality are presented. A polybenzoxazole (PBO) containing hexafluoroisopropylidene (HFIP) side groups exhibited an intense purple PL with a quantum yield, ΦPL, of 0.22 (22%), owing to the effectively disturbed concentration quenching (CQ) in the fluorophore units by the bulky HFIP side groups. The chain ends of a wholly cycloaliphatic polyimide (PI), derived from 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) and 4,4′-methylenebis(cyclohexylamine) (MBCHA), were modified with conjugated monoamines. The PI derived from 2,3,6,7-naphthalenetetracarboxylic dianhydride (2,3,6,7-NTDA) and MBCHA exhibited a very high glass transition temperature (Tg = 376 °C) and purple fluorescence from the S1(π,π*) state. However, its ΦPL value was lower than expected. A pronounced effect of fluorophore dilution using CBDA on the PL enhancement was observed. This is closely related to the planar structure of the 2,3,6,7-NTDA-based diimide units. By contrast, the counterpart using an 2,3,6,7-NTDA isomer, 1,4,5,8-NTDA, was virtually non-fluorescent, despite its sufficient dilution using CBDA. The PI film obtained using 3,3″,4,4″-p-terphenyltetracarboxylic dianhydride (TPDA) with a non-coplanar structure and MBCHA exhibited an intense blue fluorescence spectrum (ΦPL = 0.26) peaking at 434 nm. The dilution approach using CBDA enhanced its fluorescence up to a high ΦPL value of 0.41. Even when TPDA was combined with an aromatic diamine, 2,2′-bis(trifluoromethyl)benzidine (TFMB), the intense blue fluorescence was observed without charge-transfer fluorescence. A semi-cycloaliphatic PI derived from TFMB and a novel cycloaliphatic tetracarboxylic dianhydride, which was obtained from a hydrogenated trimellitic anhydride derivative and 4,4′-biphenol, was used as another host polymer for 9,10-bis(4-aminophenyl)anthracene (BAPA). The BAPA-incorporating PI film resulted in a significant PL enhancement with a considerably high ΦPL of 0.48. This PI film also had a relatively high Tg (265 °C). A reactive dye, N,N′-bis[4-(4-amino-3-methylbenzyl)-2-methylphenyl]-3,4,9,10-perylenetetracarboxydiimide, was harnessed as a fluorescence probe to explore transamidation between polyimide precursors in solution.